2016
DOI: 10.1093/icesjms/fsw197
|View full text |Cite
|
Sign up to set email alerts
|

Survival, growth, and morphology of blue king crabs: effect of ocean acidification decreases with exposure time

Abstract: Ocean acidification is an altering marine carbonate chemistry resulting in potential effects to marine life. In this study, we determine the effects of decreased pH on the morphology, growth, and survival of juvenile blue king crab, Paralithodes platypus. Crabs were reared at three pH levels: ambient (control, pH ∼8.1), pH 7.8, and pH 7.5, for 1 year and monitored for morphological changes, survival, and growth. Exposure to seawater at pH 7.8 had no effect on morphology or mortality and had only a minor effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…tumida appears to be resilient to moderate pH reductions, at least over the time-scale of this experiment. Length of exposure to reduced pH conditions is an important factor because some species take as long as a year to reveal measurable effects 58 , while others do so in as little as 3 weeks 11 . The natural environmental variability within this species’ range may factor heavily in their resilience, as coastal waters off California are thought to be naturally stressful because of changes in temperature and calcite saturation states that result from upwelling events 59 .…”
Section: Discussionmentioning
confidence: 99%
“…tumida appears to be resilient to moderate pH reductions, at least over the time-scale of this experiment. Length of exposure to reduced pH conditions is an important factor because some species take as long as a year to reveal measurable effects 58 , while others do so in as little as 3 weeks 11 . The natural environmental variability within this species’ range may factor heavily in their resilience, as coastal waters off California are thought to be naturally stressful because of changes in temperature and calcite saturation states that result from upwelling events 59 .…”
Section: Discussionmentioning
confidence: 99%
“…They found that the effect of reduced pH/elevated pCO 2 on exoskeleton mineral composition was small in mid-intertidal species relative to low-intertidal species, and interpreted this as indicating that adaptation to the variable intertidal zone in these crabs is associated with tolerance to OA, at least when it comes to maintaining their mineralized structures. Long et al (2017) determined the effects of a 1-year exposure to decreased pH ($8.1, 7.8, 7.5) on the morphology, growth, and survival of juvenile blue king crab, Paralithodes platypus. They found no effect of pH 7.8 on morphology or mortality and only a minor effect on growth.…”
Section: The Contributions In This Theme Issuementioning
confidence: 99%
“…Several species are key predators that recycle carbon from benthos to the nekton and provide biotic resistance against invasive species (Baird and Ulanowicz, 1989;Silliman and Bertness, 2002;DeRivera et al, 2005;Boudreau and Worm, 2012). They have significant economic importance for commercial and recreational fisheries across the global and regional scales, from the U.S. West coast and polar regions (Hodgson et al, 2016;Long et al, 2017;Pacific States Marine Fisheries Commission, 2019), to the Gulf and Atlantic coasts (Tomasetti et al, 2018), North Atlantic (Agnalt et al, 2013), and tropical regions (Stentiford et al, 2012). Understanding effects of OA on this group is important, as negative responses to OA could have drastic ecological impacts and socio-economic implications.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining biomineralization under OA may come with high energetic costs, causing organisms to divert energy from vital physiological processes, such as reproduction (Long et al, 2013a;Meseck et al, 2016), and growth (Wood et al, 2008). The aerobic metabolic responses to reduced environmental pH are extremely variable in most invertebrate phyla; some marine decapods are highly tolerant to OA stress, which can be mainly attributed to their capacity for acid-base regulation that allows the organisms to buffer disruptions to internal pH (Small et al, 2010;Long et al, 2017). The maintenance of hemolymph pH (pH e ) has a potential to be a strong indicator of organismal homeostasis (Truchot, 2012) in response to changing carbonate chemistry.…”
Section: Introductionmentioning
confidence: 99%